CFD simulation of a thermoacoustic engine with coiled resonator - Zink, Florian; Vipperman, Jeffrey; Schaefer, Laura (International communications in heat and mass transfer, 2010)
Thermoacoustic energy conversion is based on the Stirling cycle. In their most basic forms, thermoacoustic devices are comprised of two heat exchangers, a porous medium, both placed inside a resonator. Work is created through the interaction of strong sound waves with the porous medium that is subject to external heating. This work explores the effect of resonator curvature on the thermoacoustic effect. A CFD analysis of a whole thermoacoustic engine was developed and the influence of a curved resonator on the thermoacoustic effect is discussed. The variation of pressure amplitude and operating frequency serves as metrics in this investigation. It was found that the introduction of curvature affects the pressure amplitude achieved. Severely curved resonators also exhibited a variation in operating frequency.